The relationship between mirror-touch synaesthesia and empathy: New evidence and a new screening tool. Issue 5 (18th August 2018) - Ward, Jamie; Schnakenberg, Patricia; Banissy, Michael J
ABSTRACT: People with mirror-touch synaesthesia (MTS) report tactile sensations on their own body when seeing another person being touched. Although this has been associated with heightened empathy and emotion perception, this finding has been disputed. Here, we conduct two experiments to explore this relationship further. In Experiment 1, we develop a new screening measure for MTS. We show that MTS is related to vicarious experiences more generally, but is not a simple exaggerated version of normality. For example, people with MTS report videos of scratching as "touch" rather than "itchiness" and have localized sensations when watching others in pain. In Experiment 2, we show that MTS is related to increased emotional empathy to others and better ability to read facial expressions of emotion, but other measures of empathy are normal. In terms of theoretical models, we propose that this is more consistent with a qualitative difference in the ability to selectively inhibit the other and attend to the self.